Fallow lands of plenty : public schools as leaders in rural food system relocalization - Klein, Eric A. (Emerald Publishing Limited : IAP | Information Age Publishing, Inc., 2023)
"Can public schools feed themselves? That deceptively simple question is like a fingernail picking at a fray in the fabric of 21st century public education. Fallow Lands of Plenty chronicles one high school's attempt to feed itself and, in doing so, unravels the fabric of neoliberal education, exposes its logics of dependence and control, and begins to weave a new tapestry of education for community cooperation and resilience. Set during the ongoing transition between post-industrial globalization and the community structures that are to come, this rich narrative moves from furrows of Appalachian red clay soil, to the mountaintop homesteads of elder seed savers, to the conveyor belts of sterilized food sorting machines, and, finally, to a school's cafeteria on the day that 250 portions of student-grown sweet potatoes were served. Along the way, Fallow Lands centers knowledges of place as well as the literal and metaphorical seeds of relocalized food and education systems. Critical and theoretically informed, the text disobeys the values, purpose and canon of public education and proposes a fledgling pedagogy to address the challenges of the coming age"-- Provided by publisher.
Keywords: Education, Rural -- Appalachian Region, Southern -- Case studies.; Place-based education -- Appalachian Region, Southern -- Case studies.; Food supply -- Appalachian Region, Southern -- Case studies.; Local foods -- Appalachian Region, Southern -- Case studies.; Education -- Student Life & Student Affairs.; Educational administration and organization.; Student life.; elektronické knihy; electronic books